The Sanskar vidhi = The procedure of sacraments of Swami Dayanand Saraswati - Dayananda Sarasvati, Swami, 1824-1883 (Sarvadeshik Arya Pratinidhi Sabha, 1976)
On the Hindu sacramental rituals setting forth the Arya Samaj considerations.